Effects of practicing V2 skating with a flight phase on the skating velocity of female cross-country skiers - Fujita, Z.; Tsuchiya, J. (Sport Science Research, 2012)
This study attempts to clarify how the guidance and training of V2 skating that intentionally includes a flight phase affects the skating velocity of female cross-country skiers. The test subjects were five female skiers who did not have any flight phase in their regular V2 skating practice. In the experiment, the test subjects were first asked to perform a practice jump without a flight phase after a 20 m skate and their velocity was recorded. They were trained to glide with flight phases for about 10 minutes and then asked to do a practice jump with flight phases. In the test, the subjects used poles and skies equipped with force sensors to measure the forces of the poles and skies. After the test, each skier was interviewed about how she felt skating un er those circumstances. The result of experiment showed that the training caused all skiers to change their skating style to V2 skating with flight phases. Moreover, in the skating attempts with flight phases, the skating velocity and the peak and average forces of the pole and ski significantly increased. The interviews revealed that three subjects felt a sense of fear as they were airborne and that four subjects felt a near loss of balance. These results suggest that practicing skating with flight phases was effective in increasing the skating velocity of the female skiers. Moreover, it was difficult for the female skiers to learn to skate with flight phases through a normal training method because of the sense of fear that they experienced during the maneuver.